Label-free biosensors based on in situ formed and functionalized microwires in microfluidic devices. Issue 23 (15th October 2015) - Xing, Yanlong; Wyss, Andreas; Esser, Norbert; Dittrich, Petra S.
Abstract : Label-free biosensors based on in situ formed and functionalized TTF–Au wires were developed using an integrated microfluidic system. Abstract : Label-free biosensors based on in situ formed and functionalized TTF–Au wires were developed using an integrated microfluidic system. By applying different modification protocols, TTF–Au wires were successfully used for sensitive label-free detection of catecholamines and human IgG by Raman spectroscopy.